Does gender and ankle injury history affect weightbearing dorsiflexion in elite artistic gymnasts? - Miller, H.; Fawcett, L.; Rushton, A.. (Physical Therapy in Sport, 2020)
To establish normative data for weightbearing dorsiflexion (WBDF) in elite artistic gymnasts. Design: Quasi-experimental design with descriptive analysis (mean, SD, 95% CI). Use of independent t-test to analyse gender differences, and dependent t-test to analyse WBDF injured limb compared to contralateral uninjured limb. Setting: Data Collection at British Gymnastics Lilleshall National Sports Centre during national squad training camp. Participants: 55 Participants of the British Gymnastics National Artistic Squad (27 male and 28 female). Main outcome measure: Weightbearing lunge test to measure WBDF using a digital inclinometer. Results: There was no significant difference (p > 0.05) for gender and WBDF, although females had less range and greater variability (female mean ± SD = 45.0°±6.8°, 95% CI 42.6°, 47.6°; male mean ± SD 45.6°±5.4°, 95% CI 43.7°, 47.6°). There was a significant difference (t[23] = -3.259, p < 0.05) for previous injury and WBDF (uninjured mean ± SD 47.4°±5.7°, 95% CI 45.0°, 49.8°; injured 45.1°±6.0°, 95% CI 42.6°, 47.7°). Conclusions: Gymnasts with a unilateral injury history have significantly less WBDF in the injured limb compared to the contralateral uninjured limb. Females have less WBDF than males, however this was not significant. Further research is needed to establish if this deficit in WBDF after injury is an issue during gymnasts` landings.